Koizumi carried the day: Did the Japanese election results make people happy and unhappy? - Yoshiro Tsutsui; Miles Kimball; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2007)
This paper investigates whether Japanese people were happy and unhappy with the general election conducted on September 11, 2005, in which the Prime Minister, Koizumi, won a landslide victory. We conducted a large survey just after the election to ask people how happy they were and which party they had supported. Although there are consistent tendencies that supporters of ruling parties were happier and supporters of opposition parties were unhappier, the effect was not significant. Considering the results of a previous study that showed that Americans demonstrated significant responses to the result of a presidential election, this study suggests that Japanese people are indifferent to politics.
Keywords: I31; D72; C42; 330; election; happiness; Koizumi Cabinet; survey; Japan; Wahlverhalten; Zufriedenheit; Schätzung; Japan